2011
DOI: 10.1007/s00395-011-0163-2
|View full text |Cite
|
Sign up to set email alerts
|

EGFR trans-activation by urotensin II receptor is mediated by β-arrestin recruitment and confers cardioprotection in pressure overload-induced cardiac hypertrophy

Abstract: Urotensin II (UTII) and its seven trans-membrane receptor (UTR) are up-regulated in the heart under pathological conditions. Previous in vitro studies have shown that UTII trans-activates the epidermal growth factor receptor (EGFR), however, the role of such novel signalling pathway stimulated by UTII is currently unknown. In this study, we hypothesized that EGFR trans-activation by UTII might exert a protective effect in the overloaded heart. To test this hypothesis, we induced cardiac hypertrophy by transver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 50 publications
1
49
0
Order By: Relevance
“…28,29 Our data support this hypothesis. The partial loss of cardiomyocyte Morphology of aortas and intramyocardial arteries ex vivo and estimation of wall stress, respectively.…”
Section: Discussionsupporting
confidence: 82%
“…28,29 Our data support this hypothesis. The partial loss of cardiomyocyte Morphology of aortas and intramyocardial arteries ex vivo and estimation of wall stress, respectively.…”
Section: Discussionsupporting
confidence: 82%
“…However, the mechanism by which PID1 mediates its effects during the transition from cardiac hypertrophy to failure remains elusive. It is generally accepted that a mechanical signal induced by pressure overload will initiate a cascade of biological signaling transduction pathways that increase collagen synthesis and cardiomyocyte growth [13,14,15,16,17]. Previous studies have demonstrated that the AKT pathway is crucial in the process of cardiac hypertrophy [18,19,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, arrestin-2-dependent ERK activation mediated protective effect of glutamate acting via metabotropic glutamate receptor 1 (mGluR1) against serum-deprivation-induced apoptosis (Emery et al 2010). Both arrestin-2 and arrestin-3 mediate transactivation of the epidermal growth factor (EGF) receptor by the Gq-coupled receptor of neuropeptide urotensin II (Esposito et al 2011). Urotensin II, which is expressed in the nervous, cardiovascular, and urogenital systems, and its receptor are upregulated in the pathological heart (Zhu et al 2006), and this increase seems to be protective, since treatment with urotensin II antagonist exacerbates heart pathology and promotes apoptosis of cardiomyocytes, the effect linked to reduced EGF receptor transactivation and resulting ERK activity (Esposito et al 2011).…”
Section: Arrestins Regulate Apoptosis Via Signaling Mechanismsmentioning
confidence: 99%
“…Both arrestin-2 and arrestin-3 mediate transactivation of the epidermal growth factor (EGF) receptor by the Gq-coupled receptor of neuropeptide urotensin II (Esposito et al 2011). Urotensin II, which is expressed in the nervous, cardiovascular, and urogenital systems, and its receptor are upregulated in the pathological heart (Zhu et al 2006), and this increase seems to be protective, since treatment with urotensin II antagonist exacerbates heart pathology and promotes apoptosis of cardiomyocytes, the effect linked to reduced EGF receptor transactivation and resulting ERK activity (Esposito et al 2011). Arrestin-3 mediated the protection conferred by the angiotensin II receptor 1A to primary rat vascular smooth muscle or to HEK293 cells against hydrogen peroxide (H 2 O 2 )- or etoposide-induced apoptosis (Ahn et al 2009).…”
Section: Arrestins Regulate Apoptosis Via Signaling Mechanismsmentioning
confidence: 99%